Determinanty migracji zagranicznych mieszkańców regionu podlaskiego - Kukulak-Dolata, Iwona (Determinants of the Labour Migration of Residents from Podlasie Region, 2009)
The paper is an attempt to find the answer to the issue of commercial migration of the residents from Podlasie region. This region is according to the National Census of Population the second one in Poland where the migration is on the biggest scale converted 1000 residents. After accession to the EU, the migration has increased. Therefore it is of great significance to find out the cause of the migration and its character. For this purpose, there were used some surveys based on questionnaires conducted on 500 people sample, 236 out of them at the moment of questioning were staying abroad. In this article, the scale of the migration, labour migrants characteristics, the duration of stay abroad and expecting advantages for working abroad were taken into account. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 196-203